Eksistesialisme Menurut Maria Montessori Dalam Pendidikan Anak Usia Dini - Hafidz, Nur; Maemonah; Baryati (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2023)
Little humans have great potential, develop optimally by involving teachers, parents and children. Teachers and parents contribute to early childhood education (PAUD) services applying various lessons and curricula according to their basis. In this study, it examines the idea of ​​existentialism according to Maria Montessori in Early Childhood Education. This study used a library research method which refers to the data sources on Montessori existentialism in early childhood education. Research is empirical and theoretical by examining theories on objects and phenomena that are the focus of research from rational expressions of ideas. The results of the study describe the thoughts of children that have an impact on the training of daily life skills, sensory training, and children's language development. then in the concept of PAUD existentialism according to Maria Montessori emphasizes learning and curriculum through children's experiences that naturally involve the roles of teachers, students, and parents. The impact of Montessori existentialist thinking is respect for the child, the mind that absorbs the child, and the environment that is ready. This has an impact on the substance of Montessori-based existentialism.